Cardiometabolic Risk and Female Sexuality: Focus on Clitoral Vascular Resistance. Issue 11 (1st November 2016) - Maseroli, Elisa; Fanni, Egidia; Cipriani, Sarah; Scavello, Irene; Pampaloni, Francesca; Battaglia, Cesare; Fambrini, Massimiliano; Mannucci, Edoardo; Jannini, Emmanuele A.; Maggi, Mario; Vignozzi, Linda
ABSTRACT: Introduction: The relation between sexual and cardiovascular health in women is not well defined. Clitoral color Doppler ultrasound (CDU) with assessment of the pulsatility index (PI), reflecting resistance to blood flow, has been proposed as an objective measurement of sexual functioning. Aim: To investigate associations between clitoral PI and cardiometabolic risk factors, sexual and intrapsychic parameters, and self-perception of body image. Methods: Seventy-one adult heterosexual women in a stable relationship attending our clinic for sexual dysfunction were consecutively recruited. Main Outcome Measures: Patients underwent physical, laboratory, and clitoral color Doppler ultrasound examinations and completed the Female Sexual Function Index, the Middlesex Hospital Questionnaire, and the Body Uneasiness Test (BUT). Results: Clitoral PI was positively correlated with body mass index (r = 0.441, P < .0001), waist circumference (r = 0.474, P < .0001), glycemia (r = 0.300, P = .029), insulin (r = 0.628, P = .002), homeostatic model assessment index (r = 0.605, P = .005), triglycerides (r = 0.340, P = .011), total cholesterol (r = 0.346, P = .010), and low-density lipoprotein cholesterol (r = 0.334, P = .016). All relations, with the exception of glycemia, retained statistical significance after adjusting for age, smoking habit, and years since menopause ( P < .0001 for body mass index, waist circumference, and triglycerides; P < .05 for all other associations). Analysis of covariance, after adjusting for confounders, showed that women with obesity or metabolic syndrome (MetS) showed significantly higher PI values (obesity: F = 17.79, P = .001; MetS: F = 7.37, P = .019). In particular, a stepwise increase of PI was found as a function of increasing MetS components (β = 0.434, P = .007). Clitoral PI was negatively associated with Female Sexual Function Index arousal (β = −0.321, P = .014) and satisfaction (β = −0.289, P = .026) scores and positively associated with Middlesex Hospital Questionnaire somatized anxiety symptoms, even after adjusting for age, smoking habit, years since menopause, and current use of psychiatric medication (β = 0.354, P = .011). A positive association also was observed between PI and the BUT positive symptom distress index (β = 0.322, P = .039) and BUT for dislike of the womb, genitals, and breast (β = 0.538, P < .0001; β = 0.642, P < .0001; β = 0.549, P < .0001, respectively). After introducing waist circumference as another covariate, the associations between clitoral PI and the BUT positive symptom distress index and BUT dislike of the womb, genitals, and breast retained statistical significance ( P = .038 for positive symptom distress index; P < .0001 for dislike of womb, genitals, and breast). Conclusion: Clitoral vascular resistance is positively associated with MetS (in particular insulin resistance), decreased sexual arousal, body image concerns, and increased somatized anxiety symptoms. Further studies are needed to establish whether treatment of metabolic abnormalities might improve clitoral color Doppler ultrasound indices and sexual outcomes.